Contrast of a Reliability Model of Social Function of Emotions for Public Safety - Carreón Guillén, Javier (Consorcio de Universidades Mexicanas A.C., 2014)
State and society have shifted from coercive relations totalitarian to democratic persuasive governance in which citizens participate in evaluating the actions of their rulers. In public safety, civil society has been divided into two sectors: observatories and vulnerable citizens. The first sector has built a dialogue with their leaders while evaluating their performance and from management sets priorities for crime prevention and combating crime. However, it is vulnerable sector in the civil sphere where a range of emotions which the present work has considered paramount to contrast a distrust of authorities based on negative emotions are conceived model. For this purpose, we conducted a cross-sectional study with a nonrandom sample of 270 residents of a community Huasteca. The analysis of normal C = 3.211), reliability (alpha > 0.60), adequacy (KMO = 0.762), sphericity (c2 = 13.14; 11gl, p < 0.001), validity (Φ > 0.300), covariance (0.90 < Φ > 0.10) and fit (c2 = 1.438; 3gl, p < 0.697, GFI = 0.987, RMR = 0.042; Holter = 240, p < 0.05; PRATIO = 0.300) show that the structural model paths can be specified to explain the relationship between concern and distrust (β = 0.26). From these findings a discussion with the Theory of Social Reliability was performed.